Remarkable response to CDK4/6 inhibitor–based endocrine therapy in HR+/HER2− metastatic male breast cancer with visceral crisis: a case report - Liu, Jianfeng; Chen, Wei; Wang, Jian; Wang, Xianchen (Frontiers in Oncology, 2026)
Male breast cancer (MBC) is rare, and visceral crisis is an exceptionally uncommon yet life-threatening presentation in this population. Although current guidelines recommend combination chemotherapy as first-line therapy for visceral crisis, responses are often inadequate, and evidence for alternative approaches in men is scarce. We report a case of HR+/HER2- metastatic MBC complicated by visceral crisis. Despite first-line chemotherapy, the patient showed swift clinical worsening accompanied by radiographic progression. In view of the lack of treatment response, a CDK4/6 inhibitor–based endocrine regimen was initiated, achieving substantial tumor regression and prolonged disease control. This case suggests that CDK4/6 inhibitor–based endocrine therapy can induce meaningful disease reversal even in visceral crisis and may be a feasible option for selected HR+/HER2− MBC patients after chemotherapy failure. Our case suggests that CDK4/6 inhibitor–based endocrine therapy may offer clinical benefit even in the setting of visceral crisis after chemotherapy failure, indicating that treatment sequencing in such scenarios may merit further consideration.